Políticas de ações afirmativas na Universidade do Estado do Rio de Janeiro (UERJ): o curso de Pedagogia em debate - Abreu, Elisangela Nunes do Nascimento de (Universidade Federal de São Carlos, 2018)
The objective of this research was to analyse which initiatives and repercussions with regard to the democratization of the affirmative policies of action about the admission and continuity in the college education of the degree course of the Pedagogy of UERJ, in accordance with the 12.711/12 law though the prevailing professors outlook of the recurrence painted out and forwarding demanded for the attendance to the students from the reading of your institutional reality. The central points of the leading me course are: a) affirmative action policies in international experiences; b) the contextualization of affirmative action policies within the framework of Brazil's public educational policies; c) explaining the genesis, development and deployment of education policies actions in the UERJ and d) discuss in the light of the prevailing speeches the perspective of the professors of the Pedagogy of UERJ a reading between proposition, actions and demands. The theoretical methodological axis was preliminarily a bibliographical and documentary survey through the Bank of theses and dissertations of CAPES and the institutional repository of documentary base of UERJ. The Collective Subject Discourse (DSC in Portuguese) was used as an analytical theoretical framework, which emphasis was to situate and filter incidences of discourses, recurrences and demands, guided by the quanti-qualitative approach and in this section, the case study, considering that the UERJ is the local epistemological research. As one of the instruments of data collection, interviews were chosen through a semi-structured script, preceded by characterization of the respondents. We had 17 returns as the respondents set, that is, professors who work with disciplines in the Pedagogy course. In the procedural scope, we use the documentary analysis technique (CELLARD, 2010) regarding UERJ records and initiatives and more specifically the pedagogy course in the referral of the recurrences to attendance, debate and reflection on the affirmative action policies within it. Regarding the data collection technique, the interviews helped us to understand the respondents' perception of the meanings and meanings that were triggered within the pedagogy course in the reality of UERJ (POUPART, 2010), followed by content analysis (BARDIN, 2009) and Collective Subject Discourse (LEFEVRE, 2014). Through the return of the respondents, it was verified that the affirmative action policies implemented in 2002/2003 the UERJ selection process through the statutes 3524/00 and 3708/01 and continue to fulfill their objectives of providing population access to university education, but in the Pedagogy course, due to low competition, the access to the course is seen in a simple way. Professors, for the most part, know the quota system and support it. They report that there was no impact of the quotas reflected in the classroom, because they reach their goals in the classroom and they do not notice a difference between the student and non-quotators, because the difficulties presented in the first moments are general, having the coordination of the course as support to the students as voluntary initiatives of teachers. However the inclusion to the university education is a subject that do not requires only suitability programs of the inclusive ones, are effective necessary polices to the non exclusion of the expropriated in a social and economic way.
Affirmative action policies in Rio de Janeiro State University (UERJ): the course of Pedagogy in debate
Keywords: Políticas de ações afirmativas; Democratização da educação superior; UERJ; Programas de ação afirmativa; Affirmative action programs; Democratization of higher education; Universidade do Estado do Rio de Janeiro; CIENCIAS HUMANAS::CIENCIA POLITICA::POLITICAS PUBLICAS; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL; CIENCIAS HUMANAS::CIENCIA POLITICA::POLITICAS PUBLICAS::ANALISE INSTITUCIONAL